Pengaruh Web E- Learning Dan Lingkungan Sekolah Terhadap Hasil Belajar Siswa/ Siswi Pada Mata Pelajaran PendidikanAgama Islam Di SMA Negeri 2 Kota Tebing Tinggi - Dwiyanti, Elva; Nasution, Herry Syahbannuddin; Sazali, Anwar (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
The Purpose of This Research Is To: (1) Determine the Significant Influence of Web E-Learning on Student Learning Outcomes at SMA Negeri 2 Tebing Tinggi City, (2) Determine the Significant Influence of School Environment on Student Learning Outcomes at SMA Negeri 2 Tebing Tinggi City, (3) Determine the Significant Influence Between Web E-Learning and School Environment on Student Learning Outcomes at SMA Negeri 2 Tebing Tinggi City. To achieve the above objectives, this researcher uses a quantitative research type. The data collection technique used in this study is a questionnaire. The subjects in this study were students of class XI IPA 1 to XI IPA 5 totaling 152 students (respondents). The data analysis techniques used were instrument test analysis, prerequisite test, regression test, hypothesis test. The test results for the web e-learning variable showed a t-count value of 3.443 and a significant value of 0.01, thus t-count> t table (3.443> 1.654) and a significant value of 0.01 <0.05. So according to the partial hypothesis test criteria, the first hypothesis is accepted, which means that there is a positive and significant influence between web e-learning on student learning outcomes at SMA Negeri 2 Kota Tebing Tinggi.Based on the results of the t-test for the school environment variable, the calculated t value was 1.241 and the sig value was 0.217.  Thus t count > t table (1.241 < 1.654 and the significance value is 0.217 > 0.05. So it can be concluded that there is no influence of the school environment on student learning outcomes at SMA Negeri 2 Kota Tebing Tinggi. Based on the F test table above, the F count is 7.413 with a significance of 0.01 while the F table value for N = 155 df-n-1 (155-2-1-152) so N 152 is .... The Ho test criteria are rejected if the F count <F table and the significance value < a (0.05). Therefore, the F count (7.855) > F table (3.05) and the significance value (0.001) < a (0.05). So it can be concluded that Ho is rejected and Ha is accepted. This proves that the hypothesis that there is a significant positive influence of web e-learning and school environment on student learning outcomes is accepted. Therefore, it can be concluded that the variables web e-learning and school environment  Simultaneously, it has an effect on student learning outcomes. This means that the more optimal the e-learning website used in the learning process, the better the learning outcomes will be.